Ushul Fiqh on the Evidences of Interfaith Marriage: An Islamic Education Perspective - Siregar, Hariman Surya; Nurhamzah, Nurhamzah; Siti Nurazizah, Vina Berliana; Nurfauzi, Bayu Bambang (Laboratory of Islamic Religious Education Faculty of Tarbiyah and Teacher, 2024)
The purpose of this article is to find out the law of interfaith marriage in terms of the results of ushul fiqh analysis of the arguments regarding interfaith marriage. The method used is the content analysis method (content study), by examining the ushul fiqh rules and Islamic studies related to the Quranic proposition regarding interfaith marriage. The type of data used is qualitative data, using literature study techniques in data collection. Interfaith marriage is the marriage of a Muslim with a non-Muslim. Islam has absolutely prohibited marriage with non-Muslims based on Q.S. Al-Baqarah verse 221 and Q.S. Al-Mumtahanah verse 10, seen in terms of the rules of ushul fiqh, the verse clearly has a prohibition and the origin in the prohibition shows the prohibition. However, in Q.S. Al-Maidah verse 5 a Muslim man is allowed to marry a woman of the book (Jews and Christians). However, in this day and age there is no longer someone who can be called a member of the book. Marriage with non-Muslims is better avoided, because in the ushul fiqh rules, rejecting mudharat takes precedence over taking benefits.Â Â Tujuan artikel ini untuk mengetahui hukum pernikahan beda agama dari segi hasil analisis ushul fikih terhadap dalil mengenai pernikahan beda agama. Metode yang digunakan adalah metode content analysis (kajian isi), dengan mengkaji kaidah ushul fikih dan kajian Islam berkaitan dengan dalil Al-Quran mengenai pernikahan beda agama. Jenis data yang digunakan adalah data kualitatif, menggunakan teknik studi kepustakaan dalam pengumpulan datanya. Pernikahan beda agama ialah pernikahan orang Islam dengan orang yang bukan Islam. Islam telah melarang secara mutlak pernikahan dengan non muslim berdasarkan Q.S. Al-Baqarah ayat 221 dan Q.S. Al-Mumtahanah ayat 10, dilihat dari segi kaidah ushul fikih ayat tersebut jelas terdapat larangan dan asal dalam larangan menunjukkan keharaman. Akan tetapi, dalam Q.S. Al-Maidah ayat 5 seorang pria muslim dibolehkan menikah dengan seorang wanita ahli kitab (Yahudi dan Kristen). Namun, di zaman sekarang sudah tidak ditemukan lagi seseorang yang bisa disebut dengan istilah ahli kitab tersebut. Pernikahan dengan non muslim lebih baik dihindarkan, karena dalam kaidah ushul fikih pun menolak mudharat lebih didahulukan dari mengambil manfaat.